Transdermal Drug Delivery System: A Recent Review (Asian Journal of Pharmaceutics (AJP), 2025)
Transdermal medication delivery is the first and foremost delivery of drugs since the inception of treatment forhuman beings and diseases. In the olden days all the physician focussed on two methods of administering the drugsthe first is the oral delivery next is transdermal delivery. The transdermal delivery has even more advantageousthan oral dosage forms in some aspects such as overcoming the drug degradation which happens in the entirelength of gastro intestinal tract. The removal of formulation is also easy and its application is easy without anyother major ingredients. The present review focuses on its origin, anatomy of skin, and its layers concerning thepassage of drugs, advantages, disadvantages, applications, physiological properties, biological properties, andlimitations, polymers, and various approaches for patches. The major challenge and success in dosage form isthe selection of polymers for formulation and its successful drug delivery. This article narrates the majority ofevaluation studies to be carried out for the transdermal patches such as Physicochemical evaluation - Thickness,Uniformity of weight, drug content determination, moisture uptake, flatness, folding endurance, Tack properties,tensile strength, Thumb tack test, rolling ball test, quick stick (peel tack) test, in vitro release studies, in vivostudies, percentage water vapor permeation test, human model, swellability, polariscopic examination, stabilitytesting and skin irritation study and their procedure and diagram of experimental performance was presented. Theprepared patches need to be successfully evaluated for the above tests and suitable bioavailability must be provedfor good market product. The content was also made on present available marketed products and its use such asnicotine patch as Nico dermis to help in smoking cessation, nitroglycerin patches for angina pectoris, estradiolpatches in combination with levonorgestrel as climara pro for menopausal symptoms, and some other drugs tocure diseases.